Práticas integrativas e complementares no âmbito da enfermagem: a formação profissional na região nordeste do Brasil - Cabral, Ravenna da Silva (2024)
Objective: To analyze the sociodemographic profile and professional training of nurses specializing in integrative and complementary health practices in the Northeast Region of Brazil. Method: This is a mixed methods study with a quantitative and qualitative approach, carried out with nurses from the Northeast. Data collection was carried out in two stages, using two instruments, a virtual questionnaire and an interview guide. Quantitative data analysis was performed using the Statistical Package for the Social Sciences (SPSS) version 20.0 software. And the qualitative data were analyzed using Bardin's content analysis. Results: 151 nurses from the Northeast Region participated in the research, of which 68 (45.0%) had training in PICS. There was a predominance of females 55 (81.0%), single 27 (40.0%), mixed race 34 (50.0%), Catholic 32 (47.0%), working as contract service providers 42 (58 .0%), with public employment 46 (66.0%). Highlighting Primary Care with 20 (25.0%) as a place of operation. The states that had the most nurses in the area were: Sergipe with 21 (31.0%), followed by Bahia with 18 (26.0%) and Rio Grande do Norte with 10 (15.0%). The most predominant PICS were: auriculotherapy 42 (15.90%), followed by reike 24 (9.09%) and aromatherapy 23 (8.71%). Regarding the training profile, 60 (88.0%) had a postgraduate degree, with specialization/residency being the most mentioned 37 (55.0%), followed by academic and professional master's degrees with 13 (19.0%). However, only 13 (16.0%) had specialization in PICS. Knowledge about practices occurred during their professional lives according to 30 (44.0%) participants, followed by 19 (28.0%) at graduation. Updated courses in the area predominated 1 to 3 times a year, mentioned by 34 (45.0%) nurses, followed by 27 (36.0%) whenever a free opportunity appears. Conclusion: Nurses in the Northeast specializing in PICS have a predominant profile similar to the general profile of nurses. The training of these professionals is still not widespread, with no part being studied during graduation and with a minority of professionals with postgraduate degrees in the area. This study highlighted the need for strategies to advance training, stimulating curricular changes in higher education in nursing, with the aim of expanding the number of professionals in this area and therefore improving teaching and the quality of assistance provided, with comprehensive and humanized care regardless of their area of activity.